Prockia jaliscana (Salicaceae), a new species from Jalisco, Mexico - Jiménez Ramírez, Jaime; Cruz Durán, Ramiro (Phytotaxa, 2018)
Prockia jaliscana is described and illustrated as a new species from the state of Jalisco, Mexico. This species is similar to P. oaxacana; however, it differs from the latter because it is dioecious, presents linear or lanceolate to foliaceous stipules, has male and female flowers different from those of P. oxacana, apetalous staminate flowers and presents an ovary with ovules in both basal and parietal placentae.